Antibody mix-and-read assays based on fluorescence intensity probes - Ujwal Patil; Atul Goyal; Binh Vu; Yanyun Liu; Vijay Maranholkar; Katerina Kourentzi; James M. Briggs; Richard C. Willson (Taylor & Francis Group, 2021)
Antibodies and Fc fusion proteins are a rapidly growing class of pharmaceuticals. Cell culture and purification process development and operation require frequent measurement of product concentrations, commonly by complex enzyme-linked immunosorbent assay and high-performance liquid chromatography methods. Here we report a fast (<30 s), and simple antibody Fc assay based on mix-and-read reporting by fluorescence emission. A soluble fluorescein-labeled Fc-affinity reporter produced by standard peptide synthesis is mixed with an Fc-containing sample to produce an immediate shift in both fluorescence polarization and intensity, compatible with on- and at-line measurements and microbioreactor monitoring. We observed significant shifts in fluorescence intensity in Chinese hamster ovary cell culture fluid spiked with IgG and detected an adalimumab biosimilar down to 100 ng/mL (10-4 g/L), despite the interferents in the complex sample matrix. Neither the fluorescence polarization nor the fluorescence intensity assay is significantly affected by the addition of clarified lysate of 2 million CHO-k1 cells/mL, suggesting applicability even to cultures of low viability. Biochemical and molecular docking approaches suggest that the fluorescence intensity enhancement is caused by changes in the fluorophore's local microenvironment upon binding to IgG Fc, especially by interactions with Fc His433.Abbreviations: CCF: Cell Culture Fluid; CHO: Chinese Hamster Ovary cells; ELISA: Enzyme Linked Immunosorbent Assay; Fc: Fragment Crystallizable of antibody; HPLC: High-Performance Liquid Chromatography; HPβCD: hydroxypropyl-β-cyclodextrin; IgG: ImmunoglobulinG; mAb: Monoclonal Antibody; PBS: Phosphate-Buffered Saline; PDB: Protein Data Bank; SpA: Staphylococcal protein A; SpG: Staphylococcal protein G.